Potensi Gen Z dalam Pengembangan Teknologi Berbasis Sistem Pertanian Presisi Guna Meningkatkan Produktivitas Pertanian di Indonesia - Gelzy Trya Wardani (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2024)
The agricultural sector is an important pillar of Indonesia's development, contributing to employment, food security, and economic growth. However, the sector's potential has not been fully utilized, with low agricultural productivity being a major problem. Factors such as the low interest of the younger generation to become farmers, lack of quality education, and limited agricultural technology are the main causes. Generation Z, with its proficiency in technology, has great potential to overcome these challenges through the implementation of precision farming, a model that uses modern technology to improve farming efficiency and yield. While the government has made various efforts, collaboration between the government and various parties, including Gen Z, is needed. Precision agriculture, which involves the use of technologies such as GPS and GIS, can increase productivity with real-time monitoring and more targeted input use. The implementation of precision agriculture also faces challenges, such as limited technological infrastructure and a lack of interest in agriculture among the younger generation. With an integrative approach, adequate education, and technological support, precision farming can be a solution to increase agricultural productivity in Indonesia, while attracting the younger generation to engage in the sector.